2019
DOI: 10.3389/fcimb.2019.00186
|View full text |Cite
|
Sign up to set email alerts
|

GDP-Mannose Pyrophosphorylase: A Biologically Validated Target for Drug Development Against Leishmaniasis

Abstract: Leishmaniases are neglected tropical diseases that threaten about 350 million people in 98 countries around the world. In order to find new antileishmanial drugs, an original approach consists in reducing the pathogenic effect of the parasite by impairing the glycoconjugate biosynthesis, necessary for parasite recognition and internalization by the macrophage. Some proteins appear to be critical in this way, and one of them, the GDP-Mannose Pyrophosphorylase (GDP-MP), is an attractive target for the design of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…GDP-Mannose Pyrophosphorylase (GDP-MP) is an enzyme involved in host–parasite recognition considered to be essential for parasite infection [ 83 , 84 ]. GDP-MPs were purified from L. mexicana ( Lm GDP-MP) and L. donovani ( Ld GDP-MP), and their enzymatic properties were compared with the human enzyme ( h GDP-MP) [ 60 , 85 , 86 , 87 ]. From a rationale design strategy including molecular modeling of 100 potential inhibitors, four compounds were identified as having a promising and specific inhibitory effect on parasite GDP-MP associated with antileishmanial activity.…”
Section: The Potential Of 2-substituted Quinolines As Antileishmanial...mentioning
confidence: 99%
“…GDP-Mannose Pyrophosphorylase (GDP-MP) is an enzyme involved in host–parasite recognition considered to be essential for parasite infection [ 83 , 84 ]. GDP-MPs were purified from L. mexicana ( Lm GDP-MP) and L. donovani ( Ld GDP-MP), and their enzymatic properties were compared with the human enzyme ( h GDP-MP) [ 60 , 85 , 86 , 87 ]. From a rationale design strategy including molecular modeling of 100 potential inhibitors, four compounds were identified as having a promising and specific inhibitory effect on parasite GDP-MP associated with antileishmanial activity.…”
Section: The Potential Of 2-substituted Quinolines As Antileishmanial...mentioning
confidence: 99%
“…Recombinant GDP-MPs from two geographically distant Leishmania species, L. donovani (LdGDP-MP) and L. mexicana (LmGDP-MP), and from human (hGDP-MP) have been previously expressed, produced, and purified, and their enzymatic properties have been characterized [16,17]. In the present work, we purified a third leishmanial GDP-MP, called LiGDP-MP, from the species L. infantum, presenting a unique amino acid difference with LdGDP-MP.…”
Section: Introductionmentioning
confidence: 99%
“…The mannosylation pathway requires the conversion of mannose into a nucleotide sugar, GDP-mannose, which is further used as a substrate by mannosyltransferases to transfer mannose on growing glycoconjugates. In this pathway, the formation of GDP-mannose is catalyzed by the GDP-Mannose Pyrophosphorylase (GDP-MP) from the substrates mannose-1-phosphate and GTP [ 6 ]. A knockout in L. mexicana demonstrated that GDP-MP is essential for amastigote survival both in vitro and in vivo [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%